Iceland : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2005)
This Report on the Observance of Standards and Codes on Data Module for Iceland highlights Data Module, response by the authorities, and detailed assessments using the data quality assessment framework. Iceland's macroeconomic statistics are generally of high quality and are adequate to conduct effective surveillance. There is a high degree of quality awareness among Iceland's statistical managers. There are some deficiencies in the periodicity and timeliness of the producer price index, and in the timeliness of central government finance statistics.